Evaluasi Kebijakan Gerakan Berkah Sampah (GBS) dalam Pengelolaan Sampah di Kabupaten Pasaman Barat - Julianti Julianti; Nora Eka Putri (Journal of Education on Social Science (JESS), 2026)
Waste management in West Pasaman Regency has not yet been effectively implemented, as reflected in low levels of community participation, limited facilities and infrastructure, and waste management practices that remain oriented toward final disposal. In response to these conditions, the local government introduced the Waste Blessing Movement (Gerakan Berkah Sampah/GBS) as a community-based waste management policy that integrates environmental, social, and economic dimensions. This study aims to evaluate the implementation of the GBS policy and to identify factors influencing its effectiveness in promoting behavioral change within the community. This research adopts a descriptive qualitative approach using a case study design. Data were collected through in depth interviews, field observations, and documentation involving key stakeholders, including officials from the Environmental Agency, technical field officers, and community members. Data analysis was conducted using the qualitative data analysis approach of Miles and Huberman, encompassing data reduction, data presentation, and conclusion drawing.The findings indicate that although the GBS policy is relevant to local waste management challenges and has been implemented since 2018, its effectiveness in changing community behavior remains limited. Public understanding and participation are uneven, socialization efforts are insufficient, and implementation is constrained by limited human resources, inadequate infrastructure, and weak monitoring and evaluation mechanisms. Nevertheless, the policy shows potential to encourage positive behavioral change, particularly among communities that actively participate and benefit from waste-based social and economic incentives. The study concludes that strengthening governance, enhancing sustainable community education, and improving coordination among stakeholders are essential to increase the effectiveness and sustainability of the GBS policy in West Pasaman Regency.